IDIOMS AND SLOGANS IN POSTER LIKE PROPAGANDA - Dvalidze, Nino (International Journal of Innovative Technologies in Social Science, 2023)
21-st century is very busy, contradictive and tensed because of several cores of wars, accordingly abundant information flows out from the internet. Nobody has time to read several pages for a long time. Minimalism in words is appreciated more. As the 12 th century renaissance period Georgian poet Shota Rustaveli said in the prologue to his famous masterpiece "The Man in the Panther’s Skin”: “A long word is told shortly” (in few words is uttered a long discourse) as “Minstrelsy is, first of all, a branch of wisdom “…So, the idioms, slogans, proverbs, parables, some other kinds of phrasal verbs and witty sayings are still the object of scientific studies as far as they have been in use side by side with ballads, poems, songs and preaches since time immemorial up today. You may meet them in modern publicist texts, in posters, in adverts, in web design as well. Therefore, interpreting the idioms adequately isn’t so easy.  It’s well known that idioms are the set of fixed expressions, which is impossible to understand directly and, in most cases, one should consult with the dictionaries of idioms.Thus, presented article’s topicality is conditioned by researching some idioms in posters for filling the information gap and developing intercultural dialogue. The methodology of investigation is qualitative, based on researching different posters, describing and analyzing.Propaganda is an attempt to inﬂuence peoples’ opinions or behavior through the use of specific images and words. It usually gives limited information which is heavily biased in its presentation. Propaganda typically achieves its aims by generating an emotional reaction in the viewer. For much of the twentieth century, public posters were a common way for governments to use propaganda to persuade their citizens. They often relied upon simple images in order to manipulate people through fear or guilt. Propaganda uses stereotypes so that audiences can readily identify which people group is the target of the poster.